PM.105 Evaluation of 10 Year Term Stillbirth Data in a Large UK Tertiary Unit Serving a Multiethnic Population. (26th April 2013) - Rehal, A; Yasmaras, B; Navti, O; Singhal, T
Abstract : Stillbirths at term can be devastating for both parents and obstetrician. In most cases the cause is unexplained. Method: Retrospective review of cases from 2000–2010 at a large UK teaching hospital. 220 cases were identified from the database. Findings: 21% of women were between 35–40 years. 10% of patients had BMI > 35. Majority of patients were white British (56%) followed by Asian (25%) background. Medical problems identified were Prexisting diabetes/developed during pregnancy (6%) and asthma (9%). 21% mothers had history of smoking. 40% of patients presented with reduced fetal movements. Most of the babies weighed between 3.1–4.0 Kg and abnormalities were identified in 10% after birth. Results from the placental histology revealed mild to moderate chorioamnionitis (13%) followed by infarction (7%) and thrombus/fibrin deposits (7%). Patients who agreed to have karyotyping, results revealed normal in 13% of cases but failed in 10%. Summary: Incidence of stillbirth can vary in multiethnic population due to socioeconomic inequalities. It is obvious that the risk is higher in obese women and those with medical problems. Identification of SGA may be one way by which antenatal care reduces stillbirth. Unexplained antepartum stillbirths accounted for 50% of cases, and a better understanding of these stillbirths is necessary to avoid the recurrence in future pregnancies.